2012
DOI: 10.1080/01431161.2012.742216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensor dependence of vegetation indices based on Hyperion and CHRIS hyperspectral data

Abstract: In previous studies of the universal pattern decomposition method (UPDM), spectral shifts, which are very common in hyperspectral imaging spectrometers, were not taken into account when calculating standard spectral pattern vectors. This study evaluated the effect of spectral shifts on the sensor dependence of the vegetation index based on the UPDM (VIUPD) and 11 other vegetation indices (VIs). Spectral shifts were calculated using Gao's spectrum-matching method. The influences of smoothing techniques (moving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…VIUPD produced the best R 2 values, indicating that it was less sensor dependent. Previous studies of VIUPD consistency between Hyperion and the Compact High Resolution Imaging Spectrometer (CHRIS), and between the Moderate Resolution Imaging Spectrometer (MODIS) and thematic mapper (TM) have been reported [21,34]. Both studies reported that VIUPD had a high consistency among the different platform sensors, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…VIUPD produced the best R 2 values, indicating that it was less sensor dependent. Previous studies of VIUPD consistency between Hyperion and the Compact High Resolution Imaging Spectrometer (CHRIS), and between the Moderate Resolution Imaging Spectrometer (MODIS) and thematic mapper (TM) have been reported [21,34]. Both studies reported that VIUPD had a high consistency among the different platform sensors, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 82%
“…However, due to the various sensor characteristics, there are differences among VIs derived from multiple sensors for the same target [10][11][12][13][14]. Therefore, multi-sensor VI continuity and compatibility are critical but complicated issues in the application of multi-sensor vegetation observations [11,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, NDVI from the bandwidth of specific satellite sensor (MODIS, in this study) may not best reflect the vegetation water status in some particular regions. VIUPD has been proved to be a sensor-independent index which can greatly avoid the effect of difference in spectral bandwidth [22,23].…”
Section: Facters Which Affect the Performance Of Viupd-derived Vcimentioning
confidence: 99%
“…Unlike the traditional broadband vegetation indices that are usually computed using the near-infrared and red bands, VIUPD is based on all observed bands. Narrowband hyperspectral data-based VIUPD has been proven to be sensitive to spectral operations and was more sensor-independent than the other 11 vegetation indices, including the NDVI and EVI [23]. VIUPD also showed great potential to discern variations in urban LST when it was used to analyze the urban heat island effect in Shijiazhuang, China [24].…”
Section: Introductionmentioning
confidence: 99%
“…The SG smoothing and MA (smoothing window of five points) techniques were adopted to reduce the influence of high-frequency noise and baseline translation noise while retaining the unique characteristics of the samples (Chen et al 2012; Zhang et al 2020). SG is the most commonly used smoothing algorithm.…”
Section: Methodsmentioning
confidence: 99%